Integrasi Aspek Lingkungan, Sosial, dan Tata Kelola dalam Praktik Hukum Bisnis Indonesia - Disurya, Ramanata; Suryati, Suryati; Sardana, Layang; Putra, Yanuar Syam; Fitra, Haidir; Munirah, Munirah (Wajah Hukum, 2025)
Environmental, Social, and Governance (ESG) in business law practice in Indonesia has become increasingly important as awareness of sustainability and corporate social responsibility grows. ESG encompasses three main aspects: environmental, social, and governance, all of which influence business and investment decisions. The environmental aspect is regulated through Law No. 32 of 2009 on Environmental Protection and Management, which mandates environmental impact assessments (AMDAL). The social aspect includes regulations such as Law No. 13 of 2003 on Manpower and Financial Services Authority Regulation No. 51/POJK.03/2017, emphasizing social responsibility and workers' rights. The governance aspect is regulated by Law No. 40 of 2007 on Limited Liability Companies and Financial Services Authority regulations on good corporate governance. ESG implementation in Indonesia faces challenges, including a lack of understanding and weak law enforcement. However, initiatives from the Indonesia Stock Exchange and the private sector show significant progress. Effective ESG implementation can enhance corporate reputation, competitiveness, and access to financing, while positively impacting society and the environment. Therefore, integrating ESG into business law practice in Indonesia is a strategic step towards greater sustainability and social responsibility.